2020
DOI: 10.1080/21645515.2019.1711298
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory features and prognosis of children receiving IgM-enriched immunoglobulin (3 days vs. 5 days) as adjuvant treatment for serious infectious disease in pediatric intensive care unit: a retrospective single-center experience (PIGMENT study)

Abstract: Introduction:Although there are studies about sepsis treatment in different age groups, data on immunoglobulin-M (IgM)-enriched intravenous immunoglobulin use in pediatric intensive care units (PICUs) are limited. The aim of this study was to evaluate the clinical features and prognoses of children receiving IgM-enriched intravenous immunoglobulin to treat sepsis, septic shock, and multi-organ failure. Method: We extracted data from the medical records of 254 children who received IgM-enriched intravenous immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The retrospective PIGMENT study, which included 254 pediatric patients with a median age of 13 months with either sepsis, septic shock or multi-organ failure, compared 3-day and 5-day treatment with IgM-enriched immunoglobulin adjunctive therapy (250 mg/kg/day) ( 55 ). Although the absence of a control group precluded its inclusion in the current analysis, the study reported a significant reduction in mortality rate with longer treatment durations.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective PIGMENT study, which included 254 pediatric patients with a median age of 13 months with either sepsis, septic shock or multi-organ failure, compared 3-day and 5-day treatment with IgM-enriched immunoglobulin adjunctive therapy (250 mg/kg/day) ( 55 ). Although the absence of a control group precluded its inclusion in the current analysis, the study reported a significant reduction in mortality rate with longer treatment durations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the supplementation of all three classes seems to be a promising strategy ( 161 ). Pentaglobin has been investigated in numerous clinical trials for the adjunctive therapy of sepsis in adult ( 141 143 ) and in several trials in paediatric patients and neonates with sepsis ( 180 – 183 ). As mentioned in several reviews the additional IgM- and IgA-components in Pentaglobin mediate beneficial effects in the treatment of inflammatory diseases compared to IVIg ( 100 , 126 , 151 , 161 , 177 , 184 ).…”
Section: Iga As Therapeutic Antibodymentioning
confidence: 99%